3-Benzoyl-1-(2-methoxyphenyl)thiourea - N. Selvakumaran; M. Mary Sheeba; R. Karvembu; Seik Weng Ng; Edward R. T. Tiekink (Acta Crystallographica Section E, 2012)
In the title compound, C15H14N2O2S, the central C2N2OS moiety is planar (r.m.s. deviation of fitted atoms = 0.0336 Å). This is ascribed to the formation of an S(6) loop stabilized by an intramolecular N—H...O hydrogen bond; additional intramolecular N—H...O and C—H...S contacts are also noted. The dihedral angles between the central unit and the phenyl and benzene rings are 23.79 (7) and 29.52 (5)°, respectively. The thione S and ketone O atoms are mutually anti, as are the N—H H atoms; the O atoms lie to the same side of the molecule. Centrosymmetric eight-membered {...HNC=S}2 synthons feature in the crystal packing. The resulting inversion dimers stack along the a axis and are connected into a three-dimensional structure by C—H...O and C—H...π interactions.